TRADISI REBU DALAM MASYARAKAT KARO: EKSISTENSI DAN PEMERTAHANAN IDENTITAS BUDAYA DI ERA GLOBALISASI - Annisa Suci Ardhini; Lestari Dara Cinta Utami Ginting; Muhammad Dafitra (Bajang Institute, 2024)
The Karo tribe, which inhabits the province of North Sumatra, has a variety of traditions and cultures, one of which is the Rebu Tradition. This tradition prohibits direct communication between in-laws and sons-in-law of different genders, as well as between in-laws of different genders. In the Karo language,